Effect of Feeding Rumen Protected Choline and Rumen Protected Fat on Dry Matter Intake and Nutrient Digestibility in Periparturient Gir Cows - Chavda, Miteshkumar Ravjibhai; Savsani, Harish H.; Chavda, Jignesh A.; Karangiya, Vijay K.; Vaghamsi, Dilipkumar G.; Kansagara, Bhargav K.; Makwana, Kirti R. (Indian Journal of Animal Nutrition, 2021)
The study was carried out on 24 advanced pregnant Gir cows to know the effects of supplementing Rumen Protected Choline (RPC) and Rumen Protected Fat (RPF) alone and in combination on dry matter intake (DMI) and digestibility of nutrients. The cows were divided equally into four treatment groups (T1 to T4; n=6 each). Cows in T1 group were fed with basal diet to meet their nutrient requirement as per ICAR (2013) feeding standard. In T2 group, cows received supplementation of RPC @ 45 g/day, in T3 RPF @ 80 g/d and in T4 with RPC @ 45 g/day + RPF @ 80 g/d along with basal diet of T1, starting from 30 days before expected date of calving to 60 days postpartum. DMI (kg/d) increased significantly (p<0.01) in T2 group compared to control. However, no significant differences among the treatment groups were observed in terms of DMI kg/per 100 kg BW or DMI g/kg BW0.75.Digestibility of ether extract was observed significantly (p<0.001) higher in T2, T3 and T4 group as compared to control, while that of CP, CF and NFE were not affected in any treatment groups, whereas digestibility of DM and OM significantly increased (p<0.05) in T2 group as compared to control. It was concluded that supplementation of RPC significantly improved the DMI and digestibility of DM, OM and EE. Digestibility of EE was also improved by RPF supplementation. However, supplementation of RPF alone or in combination did not have any significant (p>0.05) effect on DMI and digestibility of DM, OM, CP, CF and NFE.